De Alice no país das maravilhas a Memórias de Emília: comparatismo e intertextualidade e tradução - Terres, Nathalia Ferreira (2021)
This dissertation has, as its study object, the literary works Memorias daEmilia(1936) by Monteiro Lobato and Alice in Wonderland by Lewis Carroll (1865), with the intention of analyzing and comparing them, regarding their linguistics, cultural and specificities in each one of these text aspects. Therefore, their characteristics and some of their characters are highlighted, considering the genre to which they are correlated: children’s literature; also, it aims to comprehend their production context, by finding issues of influence and intertextuality between them. In that way, Memorias daEmiliais correlated with Alice in Wonderland(1865) by Lewis Carroll, by verifying the occurrence of these comparative literature phenomena. Furthermore, it verifies the translation of this Carroll’s text by Lobato, considering the alteration realized by translator. To this purpose, regarding children’s literature, we searched support in the theories by Nelly Coelho (2000), Lajolo e Zilberman (2007), Hunt (2010). In relation to Translation Studies, the theorists’ texts by John Milton (2010), Lawrence Venuti (2002), Rafael Lanzetti et al. (2006) José Lambert e Hendrik Van Gorp (2011), and Itamar Even Zohar (1990) are referred to. As far as comparative literature is concerned, its theoretical basis lies on Sandra Nitrini (2010), Tania Carvalhal (1992), Kristeva’s works (2005). The results obtained show that, during the translation of Alice in Wonderland,Monteiro Lobato brought Alice closer to his character Emilia. In his text, he presents social and cultural aspects consistent with its production context, moreover receiving influence and bearing intertextuality with Carroll’s work.